Un estimateur d’erreur en relation de comportement pour les problèmes d’impact - Louf, François; Gallimard, Laurent; Pelle, Jean-Pierre (European Journal of Computational Mechanics, 2006)
In this paper we present an error estimator to control the quality of finite elements impact simulations under small strain assumption. The error measure proposed is based on an extension of the Drucker error developped for transient dynamics problems. The contact with Coulomb friction is modeled using a bipotential. The manner of building the error measure and some examples are presented.